Modulation of angular distribution of scattered ions 12C on nuclei 16O and cluster its substructures - Dyachkov, V.V.; Sidorov, Ya.V.; Yushkov, A.V.; Zaripova, Yu.A.; Dyussebayeva, K.S. (Recent Contributions to Physics, 2019)
In this paper, the authors considered the question of the experimental study of the 16-O cluster structure by decomposing the experimental angular distributions of differential cross sections into cluster diffraction modes in elastic scattering of charged particles on cluster nuclei. Experimental data on the reaction of elastic scattering 16О(12С, 12С)16О, taken from the international database EXFOR (M.P. Nicoli, F. Haas, R.M. Freeman, S. Szilner, Z. Basrak, A. Morsad, G.R. Satchler, M.E. Brandan. Universety of Hassan II), for incident particle energies of 62 MeV, 75 MeV, 80 MeV, 94.8 MeV, 100 MeV, 115.9 MeV, 124 MeV are described. The results of decomposition of experimental angular distributions of differential cross sections into cluster diffraction modes of elastic scattering of 12-C ions on 16-O nuclei, as well as using classical wave optics, calculated the angles in which the corresponding cluster structures should appear. Peaks of scattering amplitudes on various clusters were determined depending on the energy of the incident particles. At the angles corresponding to the peaks of optical scattering on alpha clusters at energies of 62 MeV, 75 MeV, 80 MeV, 94.8 MeV, 100 MeV, 115.9 MeV satisfactory agreement of the experimental data with theoretical curves was revealed. The sizes of the target nucleus and cluster substructures are determined. As a result of the fittings, it was found that the best experimental data of the differential cross sections for the angular distributions of 12-C to 16-O elastic scattering were described by theoretical curves in the concept of the 12-C and 16-O alpha-cluster structure. The resulting abnormally small radii of intranuclear alpha clusters with respect to the classical radius of free alpha particles are most likely explained by the fact that alpha clusters are in a bound state and are surrounded by nuclear matter, which leads to an increased density of matter. In addition, it is possible that the radii of intranuclear alpha clusters are reduced due to the so-called EMC effect.